ENGLISH-QURANIC CONCEPT OF RIGHTEOUSNESS AND ABERRATION A CRITICAL STUDY - Nazir Ahmad Bhutta; Zia ur Rehman (دی اسکالر)
Allah Almighty gives righteousness and aberration by His knowledge, power and wisdom. Allah Almighty does not appoint righteousness, but He wants voluntary devotion. In spite of having the power and supreme control He does not force righteousness. We have the choice of opting or rejecting righteousness.Allah Almighty has made righteousness clear to its full extent in the Holy Qur'an but, does not force to accept it and having the power of stopping mankind forcefully from, He does not do so He wants intentional righteousness. Allah Almighty has given all the means to accept or reject it. The power of logic is irrefutable fact, but if the quest for righteousness is not available then one cannot get righteousness. If the man is headstrong, egotist and reluctant then these attitudes leads to aberration. The man who is on the right path should not think that he got this by his hard work. It is only grace of Allah Almighty. Righteousness may be given to someone who is not eager of it by the grace of Allah Almighty, but aberration is only given to those who deserve it.